Effect Of Sentiment On Stock Returns: Evidence From The Gulf Cooperation Council Stock Markets - Sharmin, Rashida (2019)
Researchers have reported a significant influence of sentiment in many developing and developed markets. Due to the limited access for foreign investors, the US$900-billion-dollar GCC (Gulf Cooperation Council) regional market has failed to attract foreign investors in the past. These cannot develop unless foreign investors are interested. To attract foreign investors, the influence of sentiment on these markets need to be investigated in details. The objectives of the study are (i) to identify the influence of local sentiment in the GCC stock market, (ii) to determine the effect of firm characteristics on the relationship between the stock returns and sentiment, (iii) to detect any asymmetric effect on stock returns with respect to a shock to sentiment, and finally (iv) to investigate the influence of regional and global sentiment on the GCC markets.